Recurrent mutations within the amino-terminal region of β-catenin are probable key molecular driver events in sinonasal hemangiopericytoma - Haller, Florian; Bieg, Matthias; Moskalev, Evgeny A.; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Diessl, Nicolle; Braumandl, Karin; Brors, Benedikt; Iro, Heinrich; Hartmann, Arndt; Wiemann, Stefan; et al. (The American journal of pathology, 2015)
Sinonasal hemangiopericytoma (SN-HPC) is an uncommon, site-specific, low-grade mesenchymal neoplasm of probable perivascular myoid cell origin. In contrast to solitary fibrous tumors of soft tissue and sinonasal tract origin, SN-HPCs were recently shown to lack recurrent NAB2-STAT6 fusion variants. Other molecular alterations known to occur in some of soft tissue perivascular myoid cell neoplasms were also absent in SN-HPC; thus, the molecular pathogenesis of SN-HPCs remained unknown. Guided by whole-genome sequencing combined with RNA sequencing of an index case, we analyzed a total of six SN-HPCs for mutations within the amino-terminal region of the gene CTNNB1 (cadherin-associated protein), β 1, 88 kDa, encoding β-catenin. All six cases showed missense mutations, with amino acid substitutions clustering at positions 33 to 45, corresponding to the recognition site of the β-catenin destruction complex. Similar CTNNB1 mutations have been described in a variety of epithelial and mesenchymal neoplasms. These mutations prevent β-catenin phosphorylation and proteasomal degradation but promote its nuclear accumulation and subsequent increased transcription of Wingless-related integration site target genes. Consistent with these molecular findings, β-catenin IHC showed consistent diffuse and strong nuclear staining of the tumor cells in all six SN-HPCs. Our results highlight, for the first time, CTNNB1 mutations as the likely initiating molecular events driving SN-HPC tumorigenesis, which places SN-HPC among the growing family of β-catenin-driven mesenchymal neoplasms.
Available online 4 December 2014
Gesehen am 25.03.2021